(untitled) (Research, Society and Development, 2019)
The topics involving leader and leadership are recurrent in the area of Administration, however, this subject can be studied in other environments, such as in school. In this sense, this research was carried out in the State School Francisco de Sá Cavalcante, in the city of Paulista-PB, with students of the 3rd year "A", morning shift. The aim of this article was to investigate the leadership styles of third year students and the contribution of these profiles to the formation of autonomous subjects. The research took place in a qualitative way, as it prioritized, besides bibliographical materials on the concepts of Leader, Leadership, Leadership Styles and pedagogical aspects, the students’ behavior in the classroom and the application of a questionnaire, with closed questions, in the which the student presented a perception of himself about his actions at school. It has come to the conclusion that the school has sought to make the students autonomous, helping with pedagogical proposals in the development of leaders. From the students’ perceptions about themselves and the stimuli of this school, the styles presented in this article were found.